CXCR5+CD8+ T Cells Shape Antibody Responses In Vivo Following Protein Immunisation and Peripheral Viral Infection - Tyllis, Timona S.; Fenix, Kevin A.; Norton, Todd S.; Kara, Ervin E.; McKenzie, Duncan R.; David, Shannon C.; Alsharifi, Mohammed; Yu, Di; McColl, Shaun R.; Comerford, Iain (Frontiers in Immunology, 2021)
Crosstalk between T and B cells is crucial for generating high-affinity, class-switched antibody responses. The roles of CD4+ T cells in this process have been well-characterised. In contrast, regulation of antibody responses by CD8+ T cells is significantly less defined. CD8+ T cells are principally recognised for eliciting cytotoxic responses in peripheral tissues and forming protective memory. However, recent findings have identified a novel population of effector CD8+ T cells that co-opt a differentiation program characteristic of CD4+ T follicular helper (Tfh) cells, upregulate the chemokine receptor CXCR5 and localise to B cell follicles. While it has been shown that CXCR5+CD8+ T cells mediate the removal of viral reservoirs in the context of follicular-trophic viral infections and maintain the response to chronic insults by virtue of progenitor/stem-like properties, it is not known if CXCR5+CD8+ T cells arise during acute peripheral challenges in the absence of follicular infection and whether they influence B cell responses in vivo in these settings. Using the ovalbumin-specific T cell receptor transgenic (OT-I) system in an adoptive transfer-immunisation/infection model, this study demonstrates that CXCR5+CD8+ T cells arise in response to protein immunisation and peripheral viral infection, displaying a follicular-homing phenotype, expression of cell surface molecules associated with Tfh cells and limited cytotoxic potential. Furthermore, studies assessing the B cell response in the presence of OT-I or Cxcr5-/- OT-I cells revealed that CXCR5+CD8+ T cells shape the antibody response to protein immunisation and peripheral viral infection, promoting class-switching to IgG2c in responding B cells. Overall, the results highlight a novel contribution of CD8+ T cells to antibody responses, expanding the functionality of the adaptive immune system.